2010
DOI: 10.12968/bjon.2010.19.sup4.48419
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogels and their potential uses in burn wound management

Abstract: Hydrogels are recognized as the standard treatment for necrotic or sloughy wounds. Autolytic debridement of devitalized tissue is essential to promote wound healing; this depends on the whole area being kept moist so that natural enzymatic reactions can take place. Hydrogels are considered to be gentle debriders, promoting rehydration of non-viable tissues. Hydrosorb and Hydrosorb Comfort are hydrocellular gel dressings that are made from 60% water and are therefore suitable for keeping granulation tissue and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…The lack of significant differences may be due to the fact that standard wound care using Ringer solution as well as modern wound dressings and compression therapy per se positively affects the wound healing by creating an optimized wound environment for proper wound healing (14). Thus a moist wound environment favours wound‐healing processes was established in the last decade because of the fact that in a moist wound natural enzymatic reactions can take place without disturbance (16).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of significant differences may be due to the fact that standard wound care using Ringer solution as well as modern wound dressings and compression therapy per se positively affects the wound healing by creating an optimized wound environment for proper wound healing (14). Thus a moist wound environment favours wound‐healing processes was established in the last decade because of the fact that in a moist wound natural enzymatic reactions can take place without disturbance (16).…”
Section: Discussionmentioning
confidence: 99%
“…In total, 115 studies were identified from searching the medical literature. Independent scrutiny of titles and abstracts by two authors identified 25 potentially relevant articles, all of which were excluded for the following reasons: studies undertaken in the non-pre-hospital setting (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), in clinical laboratories (26)(27)(28)(29), involving animals (30)(31)(32)(33); or published in non-English language (34)(35)(36)(37).…”
Section: Resultsmentioning
confidence: 99%
“…For example, some Australian EMS services use HBD only where water is inaccessible (57,58) or stipulate based upon patient age and/or TBSA (59), whilst one suggests several alternatives all considered appropriate (60). Variations in Australian EMS practice are replicated in overseas jurisdictions ( Table 2 Agency Numbers: [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Recommendations and Guidelines For Practicementioning
confidence: 99%
“…Now evidence is accumulating that sheet hydrogels are very useful in pain management, particularly in superficial burns, as the moisture bathes nerve endings and the smoothing and cooling nature of hydrogels helps to reduce wound pain. [88][89][90][91] However, they are not recommended for wounds with heavy exudate due to the low absorption rate, which might cause periwound maceration and bacterial proliferation. Some sheet dressings are difficult to handle because of the low mechanical strength, thereby affecting patient compliance.…”
Section: N-chloraminesmentioning
confidence: 99%